Synthesis of Polycyclic Quinazolinones through C(sp3)−H Functionalization of Inert Alkanes or Visible‐Light‐Promoted Oxidation Decarboxylation of N‐Hydroxyphthalimide Esters - Zhang, Wei‐Kang; Li, Jiao‐Zhe; Zhang, Can‐Can; Zhang, Jian; Zheng, Yan‐Nan; Hu, Yufang; Li, Ting; Wei, Wen‐Ting (European journal of organic chemistry, 2022)
Two novel C(sp3)−H functionalization of inert alkanes and visible‐light promoted oxidation decarboxylation of N‐hydroxyphthalimide (NHP) esters to access polycyclic quinazolinones have been described. These methods do not involve metal catalysts and are carried out in water or water/DMSO media. The wide substrate scope, even including the seven‐membered ring under mild reaction conditions, demonstrate the practicability of these strategies. This work describes the cleavage of the C(sp3)−H bond of inert alkanes and the visible‐light promoted oxidation decarboxylation of NHP‐esters to form alkyl radicals, which then efficiently synthesize valuable polycyclic quinazolinones through radical addition and cyclization. Both methods were carried out in water or water/DMSO media without metal catalysts with good functional group compatibility.